Combating global warming : possible rules, regulations and administrative arrangements for a global market in carbon dioxide emission entitlements (UN New YorkUS, 1994)
Examines how to implement a tradeable entitlements system for greenhouse-gas emissions, using the United Nations Framework Convention on Climate Change as the point of departure. Aims to stimulate debate by providing model rules and regulations for a tradeable carbon dioxide emission credit market.
DC